Welcome to Liberia - Ng, Yumi. (Milwaukee, Wis. : Gareth Stevens Pub., 2005)
Presents a study of the history, culture, language, and people of Liberia as well as information on their government, economy, educational system, religion and Christian holidays, Muslim and native festivals, soccer and famous players, and the arts.
Includes bibliographical references (p. 47), filmography, and index.
Horn Book.
5.9
3-6
Keywords: Liberia -- Juvenile literature; Liberia; Liberia; Liberia